A correlation gas chromatographic study of the vaporization enthalpies and vapor pressures of patchoulol and 2-tetradecanol and estimations of their sublimation properties. (July 2022) - Simmons, Daniel; Chickos, James
Graphical abstract: Highlights: The vaporization enthalpy of patchoulol and 2-tetradecanol at 298 K are evaluated. Vapor pressures at 298 K of patchoulol and 2-tetradecanol are evaluated. Sublimation and fusion enthalpies and corresponding vapor pressures for both care estimated. Abstract: The vaporization enthalpy and vapor pressure near ambient temperatures of patchoulol, present in patchouli oil, are evaluated by correlation gas chromatography. Additionally, the vaporization enthalpy of 2-tetradecanol, used initially as a standard is also evaluated using a series of 1-alkanols. While the vaporization enthalpy evaluated differs from the literature value, the vapor pressures of 2-tetradecanol are found to be in good agreement with the literature over a broad range of temperatures. Fusion enthalpies of both of these low melting substances are estimated and used to calculate their sublimation enthalpies and vapor pressures at T = ( T fus and T  = 298.15) K. The results are compared to available literature data, most of which was also estimated. Agreement with existing literature values is quite good.